PS-015 E-learning to reduce intravenous medication errors? Simulation study in a 'room of errors'. (14th February 2016) - Gschwind, L; Yankova, N; Guéguéniat-Dupessey, C; Fonzo-Christe, C; Bonnabry, P
Abstract : Background: Errors occur frequently during the medication process, from prescription to administration. They can lead to severe damage for patient health, particularly with injectable (IV) drugs. Purpose: To evaluate the impact of a self-made e-learning lesson, focused on the safety of IV drug preparation and administration, on the ability of nurses and pharmacy students to detect errors voluntarily placed in a simulated patient's room ('room of errors'). Material and methods: Selection of 11 errors related to IV drug preparation and administration based on reported incidents. Study design:number of errors detected in 15 min in the 'room of errors' by nurses and pharmacy students before and after an e-learning lesson (30 min). Evaluation of the impact of the e-learning on the mean number and type of detected errors (±SD), globally and in both populations. Satisfaction evaluation (standardised questionnaire). Results: 28 participants (16 nurses/12 pharmacy students) were enrolled. The mean number of detected errors increased significantly after completion of the e-learning (4.6 ± 2.3 vs 2.6 ± 1.8; p < 0.0001). The e-learning had a greater impact on the detection of administration errors compared with preparation errors (OR 2.8 (95% CI 1.4 to 5.5); p = 0.001). Nurses: after e-learning, the mean number of detected errors increased (5.5 ± 2.5 vs 3.3 ± 2.0; p < 0.0001). The probability of detecting a preparation error (that was not detected before e-learning) was lower (21.6%; 95% CI 12.1 to 35.8) compared with administration errors (34.7%; 95% CI 20.5 to 52.4). Pharmacy students: after e-learning, the mean number of detected errors increased (3.3 ± 1.1 vs 1.8 ± 1.1; p = 0.0001). The probability of detecting a preparation error (that was not detected before e-learning) was very low (3.8%; 95% CI 1.0 to 14.1) but higher for administration errors (27.3%; 95% CI 17.2 to 40.4). Satisfaction evaluation: most of the participants (100% of nurses, 83% of pharmacy students) appreciated this concept of learning but it was judged more suitable for nurses' practice. Conclusion: The e-learning lesson significantly improved the number of detected errors, particularly of administration errors. Long term impact and usefulness of this innovative pedagogic approach for continuing education should be evaluated in the future. No conflict of interest.